Recycling pulp mill sludge to improve soil fertility using GIS tools - Ribeiro, P. (2010)
Pulp mill sludge produced in the Cova da Beira region (Portugal) contains organic matter (11–47%), nitrogen (38–2560mg N/kg) and phosphorus (167–370mg P/kg), which may be valuable for increasing soil productivity. The levels of heavy metals are below the limits recommended by legislation and the amount of nitrogen and phosphorous to be introduced in soils does not present a risk for nutrient leaching. After identifying the environmental and technical restrictions on its application, an area of 1650 ha was identified where the sludge can be applied in forage crops, fruit trees, olive groves and vineyards. A suitable area was also found for a biosolids storage centre. The use of GIS allowed to define a sludge application index and to produce land-use suitability maps, which can be useful for sludge management.